Effect of Bekatewak Flour on Fasting Blood Glucose Levels (Study on Type 2 Diabetes Mellitus Rats Fed a High-Fat Diet) - Sufiati Bintanah; Rijzal Rusyidie; Ika Dyah Kurniati (Nutri-Sains: Jurnal Gizi, Pangan dan Aplikasinya, 2025)
High-fat diet (HFD) causes oxidative stress, which is a trigger for insulin resistance in type 2 diabetes mellitus. The provision of foods rich in antioxidants, such as rice bran, tempeh, and Javanese ginger, is needed to reduce oxidative stress. This study aimed to determine the effect of giving Bekatewak (a combination of rice bran, tempeh, and Javanese ginger) flour on fasting blood glucose levels of type 2 diabetes mellitus rats induced by HFD. This study was true experimental research using a pre- and post-test randomized controlled group design with a total of 18 rats as samples. There were three groups: the negative control group (K-), the positive control group (K+), and the treatment group (P). The study results showed a significant difference in fasting blood glucose levels before and after the administration of Bekatewak flour at a dose of 540 mg/200 g/bodyweight (p<0.05). There were significant differences in fasting blood glucose levels after intervention between K- and K+, K- and P, and K+ and P groups (p<0.001). Bekatewak flour has the potential to be developed as a functional food based on natural antioxidants to help control blood glucose levels and prevent insulin resistance caused by a high-fat diet.